The discursive construct of ngozi in Zimbabwean shona traditional worldview - Manyawu, Andrew T.; Parichi, Mandiedza (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies, 2016)
All societies continually grapple with the question of what happens to human beings after death. This has led to the construction of such concepts as heaven or paradise and hell in such a world religions as Christianity and Islam and a vast array of rituals performed from death through burial to after the burial. Shona traditional thinking has developed the concept and social practice of ngozi (angry of avenging spirit) as an element of the broader concepts of death and justice.